As tecnologias da informação e comunicação e suas utilizações na educação: análise de suas correlações e aplicações em cursos do ensino superior - Machado, Roberto (2018)
Education, whether in its formal aspect developed by educational institutions, or in any other of its forms, is increasingly approaching technology throughout its development and learning process, in a way this present work wants to show if Information and Communication Technologies (ICTs) used in education may be more or less related and aplicated in distinct college courses. In this sense, It worths to reinforce the Information and Communication Technologies are deployed in several technological tools that are also used in the education segment, including in college education. In this context, the proposal of this research was to analyze if there are technologies used more frequently in selected college education. In order to achieve this, it were used academic searching the correlation between the words "technology / information and communication technology (ICT) / technological tools" and the word "college education", as well as their combination with the names of specific courses, and in the end, three distinct higher courses were chosen: Administration, Physical Education and Medicine. Several authors of renown in the area were used as theoretical references, among them, as landmark, Vani Moreira Kenski. The present research has its nature of study classified as theoretical and has as the main objective the understanding of the exposed subject, being classified regarding its objectives as descriptive and also qualitative. The methodology made it possible to better understand the current technologies most used in the selected courses, being demonstrated that these can be adapted and used at different intensities in the different college courses, as well raising the discussion for the production of new studies in relation to the subject, wich is of extreme importance for education and for society as itself.